2001
DOI: 10.1177/070674370104600711
|View full text |Cite
|
Sign up to set email alerts
|

Peritraumatic Dissociation, Acute Stress, and Early Posttraumatic Stress Disorder in Victims of General Crime

Abstract: Ob jec tive:To com pare the re la tion be tween pe ri trau matic dis so cia tion and acute stress and the early de vel op ment of post traumatic stress dis or der (PTSD) T he re la tion be tween pe ri trau matic dis so cia tion (im me diate dis so cia tion at the time of the trau matic event) and post trau matic stress dis or der (PTSD) has been stud ied follow ing com bat ex po sure, dis as ters, criti cal in ci dents, and motor-vehicle ac ci dents. Vic tims with acute dis so cia tive symp toms ap pear to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…Due to the small sample sizes it cannot be ruled out that statistical significance for PD was not reached due to insufficient test power. However, considering the weak associations (4.6% explained variance in Birmes et al (2001a) and an uncontrolled effect size of d=.3 in Shalev et al (1998)), such an explanation appears to be less meaningful.…”
Section: Studies With Negative Outcomesmentioning
confidence: 94%
See 1 more Smart Citation
“…Due to the small sample sizes it cannot be ruled out that statistical significance for PD was not reached due to insufficient test power. However, considering the weak associations (4.6% explained variance in Birmes et al (2001a) and an uncontrolled effect size of d=.3 in Shalev et al (1998)), such an explanation appears to be less meaningful.…”
Section: Studies With Negative Outcomesmentioning
confidence: 94%
“…In the Birmes et al (2001a) study of a small sample of assault victims (N=35) the following pattern emerged. Entered in the first step of the hierarchical regression analysis, PD explained a significant proportion of PTSD symptom variance.…”
Section: Studies With Negative Outcomesmentioning
confidence: 97%
“…Of interest PDEQ levels were strongly positively associated with both peritraumatic physical and emotional reactivity, consistent with the findings of Brunet and colleagues showing that greater emotional distress and physical manifestations of anxiety are strongly associated with greater peritraumatic dissociation. Birmes et al (2001) studied 48 French crime victims within 24 h of traumatic exposure. The participants were followed to assess acute stress responses 2 weeks after the assault and posttraumatic stress at 5 weeks.…”
Section: Independent Studies Of the English Language Version Of The Pdeqmentioning
confidence: 99%
“…For example, a number of studies of individuals experiencing danger or life threat have shown specific peritraumatic dissociative changes, including alterations in time sense, perception, attentional focus, and awareness of pain among others (12, 13). In addition, depersonalization has been described in a significant percentage of individuals facing acute life threat (reviewed in 9).…”
mentioning
confidence: 99%